Electron paramagnetic resonance studies of nitrogen interstitial defects in diamond. - Felton, S; Cann, B; Edmonds, A; Liggins, S; Cruddace, R; Newton, M; Fisher, D; Baker, M (2009)
We report on electron paramagnetic resonance (EPR) studies of nitrogen doped diamond that has been (15)N enriched, electron irradiated and annealed. EPR spectra from two new nitrogen containing [Formula: see text] defects are detected and labelled WAR9 and WAR10. We show that the properties of these defects are consistent with them being the ⟨001⟩-nitrogen split interstitial and the ⟨001⟩-nitrogen split interstitial-⟨001⟩-carbon split interstitial pair, respectively. We also provide an explanation for why these defects have previously eluded discovery.